Effectiveness of Bhattacharya Instrument on Emotional Intelligence a Case Study: Cultural Influence on Emotional Intelligence in Indian Context (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Appraisal of negativeand positive emotions were elicited as most important factors of emotionalintelligence in Indian context, followed by interpersonal conflict anddifficulty, interpersonal skill and flexibility and emotional facilitation andgoal orientation. The first, second and fifth factors were related to ‘self’whereas the third and fourth factors reflected ‘interpersonal skills’. Theconstruct of emotional intelligence involved appraisal and experience ofemotion for self and interpersonal situations in valence-specific terms(positive-negative) though BEIS-In was having many similarities with theexisting emotional intelligence scales, the valence-specificity of this scaleis a unique feature. Since culture determines the acceptance, recognition,appraisal, expression of emotions to a great extent, it can be assigned thatIndian collectivist culture is responsible for this uniqueness (Bhattacharya& Sengupta, 2007).